Using Excel for business analysis a guide to financial modelling fundamentals - Fairhurst, Danielle Stein (John Wiley & Sons, 2012)
"A clear, concise, and easy-to-use guide to financial modelling suitable for practitioners at every level. Using a fundamental approach to financial modelling that's accessible to both new and experienced professionals, Using Excel for Business Analysis: A Guide to Financial Modelling Fundamentals + Website offers practical guidance for anyone looking to build financial models for business proposals, to evaluate opportunities, or to craft financial reports. Comprehensive in nature, the book covers the principles and best practices of financial modelling, including the Excel tools, formulas, and functions to master, and the techniques and strategies necessary to eliminate errors."--Publisher's website
Includes bibliographical references and index. - Print version record
Keywords: Microsoft Excel (Computer file); Corporations -- Finance -- Data processing; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Corporations; Finance; Data processing; Unternehmen; Finanzierung; Programm